2021
DOI: 10.7150/ijms.54747
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme family acts as a predict biomarker in cutaneous melanoma and indicates more benefit from anti-PD-1 immunotherapy

Abstract: The incidence of cutaneous melanoma (CM) increased since the 1970s, and also along with an unfavorable prognosis. CM patients have been verified benefits from immunotherapy, and granzymes (GZMs) comprise more than 90% of the cytolytic granules secreted by cytotoxic T lymphocytes and nature killer cell. Therefore, it is essential to evaluate the prognostic value of GZMs in CM. A total of 633 CM patients was enrolled to access the prognostic value of GZMs. The integrated prognostic value of five GZMs was validat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Among the genes downregulated in the POD24 group, GZMM and GZMK , which are commonly expressed in CTLs and NK cells, have pro‐apoptotic activities on tumor cells 45 . A low expression of GZMM and GZMK in tumor tissues has been associated with an unfavorable prognosis in cutaneous melanoma, 46 and GZMK was also found to be downregulated in the process of FL transformation 47 . Together, these results suggested that anti‐FL immune responses may be weakened in RB‐treated FL patients undergoing POD24.…”
Section: Discussionmentioning
confidence: 98%
“…Among the genes downregulated in the POD24 group, GZMM and GZMK , which are commonly expressed in CTLs and NK cells, have pro‐apoptotic activities on tumor cells 45 . A low expression of GZMM and GZMK in tumor tissues has been associated with an unfavorable prognosis in cutaneous melanoma, 46 and GZMK was also found to be downregulated in the process of FL transformation 47 . Together, these results suggested that anti‐FL immune responses may be weakened in RB‐treated FL patients undergoing POD24.…”
Section: Discussionmentioning
confidence: 98%
“…Granzymes are a family of homologous serine proteases that can induce apoptosis in various tumor cells (Anthony et al, 2010). Granzymes also encode the genes of some virtual granzymes and components of immunocytes, that are part of the cancer immune microenvironment (Wu et al, 2021). Among human granzymes, GZMA is also pivotal for the activation of immunocytes in tumors (Romero et al, 2020;Rooney et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…We explore the potential tumorigenesis mechanism of IFN-γ with TIME. The former scholars were investigated about anti-PD-1 resistance and occurrence of melanoma [51][52][53]. Hänze J, et al showed that high PD-L1-mRNA levels in tumor tissues with a positive IFN-γ signature favorably affect OS [41,54,55].…”
Section: Discussionmentioning
confidence: 99%